Ovarian follicular changes and hemodynamics in Egyptian buffaloes under CIDR-PGF2α and Ovsynch-CIDR estrus synchronization treatments - Haney SAMIR; Mohamed M.M. KANDIEL; Amal M. Abo EL-MAATY; Manila SEDIQYAR; Kazuaki SASAKI; Gen WATANABE (The Society for Reproduction and Development, 2019)
This study aimed at investigating the efficacy of two protocols of estrous synchronization on follicular changes and hemodynamics. Pluriparous Egyptian buffaloes (n = 36) were synchronized either with controlled internal drug release (CIDR)-PGF2α (7-days CIDR insert with PGF2α injected on the 6th day; n = 18) or Ovsynch-CIDR (Ovsynch protocol concurrent with 7-days CIDR insert; n = 18). Blood sampling and ovarian ultrasound examinations (Grayscale, color and power Doppler modes) were conducted on the Day of CIDR removal, estrus, and luteal phase. Mean follicle diameter (MFD), first (1st-LF) and second (2nd-LF) largest follicle diameters, and E2 levels significantly increased in the CIDR-PGF2α group at CIDR withdrawal. Ovsynch-CIDR markedly fortified higher follicle population, MFD, and 1st-LF diameter at estrus and corpus luteum (CL) volume at the luteal phase in concomitant with increases (P < 0.05) in E2 (at estrus) and P4 (at luteal phase). At CIDR removal, the blue pixels in the dominant follicle (DF) were higher (1.5 times; P = 0.054) in the Ovsynch-CIDR than in the CIDR-PGF2α. At estrus, total blood flow (TBF) and power Doppler pixels (PDP) to DF(s) were noticeably higher (seven and 1.6 times; respectively) in the Ovsynch-CIDR than in CIDR-PGF2α (5906 ± 237 vs. 830 ± 60 pixels, P < 0.01 and 5479 ± 322 vs. 3377 ± 19 pixels, P < 0.05; respectively). At the luteal phase, TBF and PDP to the CL increased in the Ovsynch-CIDR group than in the CIDR-PGF2α group (11060 ± 965 vs. 7963 ± 480 pixels, 1.4 times, P = 0.05 and 18900 ± 1350 vs. 13220 ± 568 pixels, 1.1 times, P = 0.005; respectively). In conclusion, based on the improvement in synchronized follicular activity and hemodynamics, the Ovsynch-CIDR regimen is persuaded in Egyptian buffaloes.